2016
DOI: 10.3847/0004-637x/831/1/17
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Solar-Like Oscillations, Observational Constraints, and Stellar Models for Θ Cyg, the Brightest Star Observed by the Kepler Mission

Abstract: θCygni is an F3 spectral type magnitude V=4.48 main-sequence star that was the brightest star observed by the original Kepler spacecraft mission. Short-cadence (58.8 s) photometric data using a custom aperture were first obtained during Quarter 6 (2010 June-September)and subsequently in Quarters 8 and 12-17. We present analyses of solar-like oscillations based on Q6 and Q8 data, identifying angular degree l=0, 1, and 2 modes with frequencies of 1000-2700 μHz, a large frequency separationof 83.9±0.4 μH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 154 publications
2
13
0
Order By: Relevance
“…The relative surface correction at ν max slightly improves when using the ridge centroid frequencies (ν corr (ν max )/ν max = (−1.959 ± 0.745) · 10 −3 ) over the underlying ones. The reason for the discrepancy in the surface correction is likely due to inaccurately measured frequencies in θ Cyg by Guzik et al (2016). Our even centroid frequencies agree remarkably well with a number of the radial-mode frequencies measured by Guzik et al (2016).…”
Section: θ Cygsupporting
confidence: 65%
See 1 more Smart Citation
“…The relative surface correction at ν max slightly improves when using the ridge centroid frequencies (ν corr (ν max )/ν max = (−1.959 ± 0.745) · 10 −3 ) over the underlying ones. The reason for the discrepancy in the surface correction is likely due to inaccurately measured frequencies in θ Cyg by Guzik et al (2016). Our even centroid frequencies agree remarkably well with a number of the radial-mode frequencies measured by Guzik et al (2016).…”
Section: θ Cygsupporting
confidence: 65%
“…Therefore, we only considered the radial orders for the even-and odd-degree centroids where the l=0 and l=1 modes, respectively, were measured by their respective sources. For example, Guzik et al (2016) reported 39 radial and dipole modes in θ Cyg, therefore we extracted 39 centroid frequencies from the power spectrum.…”
Section: Centroid Fittingmentioning
confidence: 99%
“…This led to several variability studies of bright stars with unprecedented photometric precision and duration of the light curves by means of customized masks (e.g. Kolenberg et al 2011;Metcalfe et al 2012;Tkachenko et al 2014;Guzik et al 2016). Meanwile, numerous bright stars are also studied with the refurbished Kepler mission K2, from co-adding carefully masked smear flux in the CCD rows of data taken with ultra-short exposure times (White et al, submitted), a technique that was verified successfully on nominal Kepler data (e.g., Pope et al 2016).…”
Section: Scattered-light Kepler Photometrymentioning
confidence: 99%
“…Simple aperture photometry (SAP) -adding all the flux contained in a window around the bleed column -has recovered light curves with precisions close to the photon noise limit. Examples treated in the nominal Kepler mission are the prototype classical radial pulsator RR Lyr (V = 7.2; Kolenberg et al 2011), the solar-like pulsators 16 Cyg AB (V ≈ 6; Metcalfe et al 2012;White et al 2013;Metcalfe et al 2015) and θ Cyg (V = 4.48; Guzik et al 2016), and the massive eclipsing binary V380 Cyg (V = 5.68; Tkachenko et al 2014). In the nominal Kepler mission SAP was only attempted for a few bright stars, and in K2 , the larger-amplitude spacecraft motion significantly increased the size of the required apertures for SAP photometry of very saturated stars, while also making their instrumental systematics more difficult to deal with.…”
Section: Introductionmentioning
confidence: 99%